2017
DOI: 10.1039/c6dt04003a
|View full text |Cite
|
Sign up to set email alerts
|

Carborane–stilbene dyads: the influence of substituents and cluster isomers on photoluminescence properties

Abstract: Two novel styrene-containing meta-carborane derivatives substituted at the second carbon cluster atom (C) with either a methyl (Me) or a phenyl (Ph) group are introduced herein along with a new set of stilbene-containing ortho- (o-) and meta- (m-) carborane dyads. The latter set of compounds have been prepared from styrene-containing carborane derivatives via a Heck coupling reaction. High regioselectivity has been achieved for these compounds by using a combination of palladium complexes [Pd(dba)]/[Pd(t-BuP)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 45 publications
1
40
1
Order By: Relevance
“…But more interestingly, the fluorescence efficiency can be tailored by changing the substituent at the adjacent Cc position, which may cause either an enhancement of the emission quantum yield or a total fluorescence quenching in the case of aromatic substituents. [11][12][13][65][66][67][68][69] Anthracene is a very well-studied -conjugate system easy to functionalize and with remarkable intrinsic photophysical, photochemical and chemical properties, which make it and its derivatives ideal molecules to construct fluorophores, fluorescent probes, organic light-emitting transistors, among others. 70,71 Throughout the last years, some carboranyl-functionalized anthracene derivatives have been reported and their photoluminescence behaviour explored.…”
Section: Introductionmentioning
confidence: 99%
“…But more interestingly, the fluorescence efficiency can be tailored by changing the substituent at the adjacent Cc position, which may cause either an enhancement of the emission quantum yield or a total fluorescence quenching in the case of aromatic substituents. [11][12][13][65][66][67][68][69] Anthracene is a very well-studied -conjugate system easy to functionalize and with remarkable intrinsic photophysical, photochemical and chemical properties, which make it and its derivatives ideal molecules to construct fluorophores, fluorescent probes, organic light-emitting transistors, among others. 70,71 Throughout the last years, some carboranyl-functionalized anthracene derivatives have been reported and their photoluminescence behaviour explored.…”
Section: Introductionmentioning
confidence: 99%
“…The 11 B{ 1 H} NMR spectra of all the compounds exhibit a triplet attributed to the ‐BF 2 unit, centered at 0.61 ppm for the aza‐BODIPYs and at 0.45 ppm for BODIPY derivatives. In addition to the ‐BF 2 resonance, those compounds bearing o ‐carborane clusters show the typical 1:1:8 or 2:8 distribution, whereas for m ‐isomers the pattern was 1:1:6:2 or 2:6:2, all of them being in the region from −3.63 to −13.70 ppm . The 13 C{ 1 H} NMR spectra of all the compounds show a resonance in the range of 41.0–43.0 ppm attributed to the benzylic carbon, and also for the Me‐carborane derivatives, the C c − C H 3 can be identified from 23.0–25.0 ppm.…”
Section: Resultsmentioning
confidence: 93%
“…Even though intense luminescence can be observed in the solution state, optical properties were often spoiled through ACQ by intermolecular interactions in the solid state. [5][6][7] It has been reported that some of the o-carborane [8][9][10][11][12][13] derivatives presented AIE [14][15][16][17][18][19][20][21] and can be applied as a solid-state luminescent material. [1][2][3] Intense solid-state luminescent properties originating from AIE were found and applied for developing the conjugated materials, including polymers.…”
Section: Introductionmentioning
confidence: 99%